Photosynthesis, growth and structural characteristics of holm oak resprouts originated from plants grown under elevated CO2 - Aranda, Xavier; Agustí, Cristina; Joffre, Richard; Fleck, Isabel (Physiologia Plantarum, 2006)
The physiological characteristics of holm oak (Quercus ilex L.) resprouts originated from plants grown under current CO2 concentration (350 μl l−1) (A-resprouts) were compared with those of resprouts originated from plants grown under elevated CO2 (750 μl l−1) (E-resprouts). At their respective CO2 growth concentration, no differences were observed in photosynthesis and chlorophyll fluorescence parameters between the two kinds of resprout. E-resprouts appeared earlier and showed lower stomatal conductance, higher water-use efficiency and increased growth (higher leaf, stem and root biomass and increased height). Analyses of leaf chemical composition showed the effect of elevated [CO2] on structural polysaccharide (higher cellulose content), but no accumulation of total non-structural carbohydrate on area or dry weight basis was seen. Four months after appearance, downregulation of photosynthesis and electron transport components was observed in E-resprouts: lower photosynthetic capacity, photosystem II quantum efficiency, photochemical quenching of fluorescence and relative electron transport rate. Reduction in ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCo) activity, deduced from the maximum carboxylation velocity of RuBisCo, accounts for the observed acclimation. Increased susceptibility of photosynthetic apparatus to increasing irradiance was detected in E-resprouts.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: CO2; Elevated CO2; Fluorescence (voyant); Growth; photosynthesis; Resprouts

Photosynthesis, growth and structural characteristics of holm oak resprouts originated from plants grown under elevated CO2 - Aranda, Xavier; Agustí, Cristina; Joffre, Richard; Fleck, Isabel (Physiologia Plantarum, 2006)
The physiological characteristics of holm oak (Quercus ilex L.) resprouts originated from plants grown under current CO2 concentration (350 μl l−1) (A-resprouts) were compared with those of resprouts originated from plants grown under elevated CO2 (750 μl l−1) (E-resprouts). At their respective CO2 growth concentration, no differences were observed in photosynthesis and chlorophyll fluorescence parameters between the two kinds of resprout. E-resprouts appeared earlier and showed lower stomatal conductance, higher water-use efficiency and increased growth (higher leaf, stem and root biomass and increased height). Analyses of leaf chemical composition showed the effect of elevated [CO2] on structural polysaccharide (higher cellulose content), but no accumulation of total non-structural carbohydrate on area or dry weight basis was seen. Four months after appearance, downregulation of photosynthesis and electron transport components was observed in E-resprouts: lower photosynthetic capacity, photosystem II quantum efficiency, photochemical quenching of fluorescence and relative electron transport rate. Reduction in ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCo) activity, deduced from the maximum carboxylation velocity of RuBisCo, accounts for the observed acclimation. Increased susceptibility of photosynthetic apparatus to increasing irradiance was detected in E-resprouts.
Keywords: CO2; Elevated CO2; Fluorescence (voyant); Growth; photosynthesis; Resprouts